Parents’ Engagement in Mathematics Learning Among Deaf Child - Liong Kon Thai; Mohd Hanafi Mohd Yasin (Department of Special Education, 2018)
Mathematics across most of the school’s subjects. The cross-sectional survey of mix method sequential explanatory was held to aim in collecting parents’ engagement in mathematics learning among deaf child from eleven constructs namely mathematical media resources support, encouragement, involvement in child’s mathematical activity, learning of mathematics experience, reading mathematical materials with child, conducive learning environment, recognition and reward, affection, expectation of child’s mathematics achievement, child acceptance and sign language mastery through questionnaires and interview protocol. The respondents were 33 parents from two Special Education National Schools deaf programs in Malaysia. Data have been analyzed through descriptive and theme analysis. The results showed that only three constructs were at the highest level of the mean, namely encouragement, affection and expectation of child’s mathematics achievement whereas others at moderate level. Therefore, parents should take some actions to help child’s mathematics learning such as increase the frequency of encouragement, emphasize the importance of mathematics, provided opportunity to apply basic mathematical facts in daily activities, visual reading materials, apply information technology, acceptance of the deaf child and strengthen the mastery of sign language. Subsequently, education ministry should pursue mathematics textbooks attached with sign language and produce mathematics exercise books in accordance with the format of examination moderation papers.